Innovation in strategic philanthropy: local and global perspectives - Anheier, Helmut K. 1954-; Simmons, Adele; Winder, David (SpringerLink Bücher, 2007)
This book is the result of case studies conducted as part of the International Network on Strategic Philanthropy, which focus on the role of philanthropy in the globalization process and in lesser developed economies. Throughout, they emphasize the lessons in innovation that can be taken from them, and together demonstrate that emerging philanthropic institutions can develop their own methods and offer criteria that the Western world might learn from.